Isoenzymic characterization of six populations of Annona cherimola Mill. from La Libertad Region, Peru - Zavala, Fátima (2009)
The aim of this study was to determinate the isozymic characteristic of six Annona cherimola populations from La Libertad Region. Leaves of trees with at least two fructifications were collected in six localities: La Cuesta, Paday, Samne, Cascas, Poroto and Trujillo. The samples were processed and the electrophoretic profiles of the enzymes PGI, APCH, MDH and ME were analyzed. We found polymorphism for the loci PGI-1 and ME, with seven and two alleles respectively, average values of 0,40 for polymorphism and mean heterozygosity between 0,206 (La Cuesta) and 0,285 (Poroto). There is high phenotypic and genotypic variability in six Annona cherimola populations in La Libertad Region.